ANALISIS POTENSI PENGHEMATAN PADA PLTU UNIT 5 DENGAN AUDIT ENERGI PADA MOTOR PEMAKAIAN SENDIRI DI PT PJB MUARA KARANG - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2017)
PT PJB Muara Karang power plant is an industry with a large electrical energy consumption for auxiliary power. In ISO50001 itensitas Energy Consumption (IKE) is a great need to audit energy consumption. In the contract the company's performance also set a percentage of personal use should not exceed 6% of the electricity production. Currently Posentase usage of own consumption at power plant unit 5 is greater than the power plant unit 4. It is necessary for an energy audit for the usage of its own in order to decrease the percentage of personal use in the power plant 5 0.5% of the current conditions and find energy savings opportunities in the power plant unit 5.To analyze this problem using energy audits, analyzes the performance test method using